PENGARUH DIGITALISASI PEMASARAN (PEMASARAN ONLINE) TERHADAP PENINGKATAN PENDAPATAN UMKM PADA PERSPEKTIF EKONOMI SYARIAH DI KOTA BANDAR LAMPUNG - Nanda Ayu Novita; Selvi Oktianingrum; Vicky F Sanjaya (Institut Agama Islam Negeri Kerinci, 2022)
Purpose: In an increasingly sophisticated era, many people use smartphones. Therefore, there must be an upgrade to carry out daily activities. All activities will be facilitated by the presence of a smartphone. Long distances will become close with the sophistication of the times. This sophistication is felt by all people, regardless of age and occupation. So in this study will analyze whether there is a good influence on online marketing by increasing UMKM income Design/methodology/approach: To get the results in this study the researchers distributed questionnaires and in data analysis using the smartpls application and using the t table. Findings: The results of this study reveal that either partially or simultaneously Service Quality and Price have an influence on service user satisfaction. Research implications: The results of the study concluded that to get an increase in income, UMKM had to upgrade their marketing strategies to make it easier for customers to order products.